Green Consumerism di Era Modern: Analisis Tren Dan Dinamika Perilaku Pembelian Berbasis Kesadaran Lingkungan - I Gst Agung Adi Tanaya; Nyoman Dwika Ayu Amrita; Ni Putu Eka Saraswati; Ni Luh Gede Vivin Apriliani (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2025)
The increasing public awareness of global environmental issues has encouraged the emergence of the green consumerism trend, or environmentally friendly consumption behavior, across various segments of society. This shift in consumption patterns occurs in response to growing environmental sustainability challenges and climate change, which demand consumers to be more responsible in selecting, using, and disposing of products. Consumers no longer consider only price and quality, but also the environmental impact of the products they consume. This study aims to analyze the concept of green consumers, identify the factors influencing green consumption behavior, and examine its implications for the modern business environment. The research method employed is a literature study (library research) using a qualitative descriptive approach, reviewing various sources such as scientific journals, books, research reports, and recent publications relevant to the topic of green consumerism. The results indicate that environmental awareness, sustainable lifestyle values, concern for ecological impacts, as well as social influence and digital media, are the main factors shaping green consumer behavior. Furthermore, the study finds that companies capable of adapting to the green consumption trend through eco-friendly product innovation, sustainable business practices, and the implementation of corporate social responsibility will gain a positive corporate image, increase consumer trust, and create competitive advantages in an increasingly environmentally conscious market.